2020
DOI: 10.3390/genes11070799
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–Phenotype Correlation in Children: The Impact of FBN1 Variants on Pediatric Marfan Care

Abstract: Currently, no reliable genotype–phenotype correlation is available for pediatric Marfan patients in everyday clinical practice. We investigated correlations of FBN1 variants with the prevalence and age of onset of Marfan manifestations in childhood and differentiated three groups: missense/in-frame, splice, and nonsense/frameshift variants. In addition, we differentiated missense variants destroying or generating a cysteine (cys-missense) and alterations not affecting cysteine. We categorized 105 FBN1-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Taniguchi et al dissect the genotype-phenotype correlations in MFS already having scoliosis and found that HI variants and variants in the neonatal region were associated with severe scoliosis and faster progression ( Taniguchi et al, 2021 ). Higher systematic scores were observed in the HI group than that in the DN group ( Stark et al, 2020 ). Striae, the stretch marks of the skin, appeared more frequently in patients with HI variants ( Faivre et al, 2007 ).…”
Section: Genotype and Clinical Manifestationsmentioning
confidence: 79%
See 1 more Smart Citation
“…Taniguchi et al dissect the genotype-phenotype correlations in MFS already having scoliosis and found that HI variants and variants in the neonatal region were associated with severe scoliosis and faster progression ( Taniguchi et al, 2021 ). Higher systematic scores were observed in the HI group than that in the DN group ( Stark et al, 2020 ). Striae, the stretch marks of the skin, appeared more frequently in patients with HI variants ( Faivre et al, 2007 ).…”
Section: Genotype and Clinical Manifestationsmentioning
confidence: 79%
“…Variants in exons 24–32 were associated with ventricular tachycardia ( Aydin et al, 2013 ). Earlier onset of pulmonary artery dilatation was found in MFS children with DN variants ( Stark et al, 2020 ).…”
Section: Genotype and Clinical Manifestationsmentioning
confidence: 97%
“…Similarly, when genotype–phenotype correlations were assessed in a pediatric cohort, missense variants affecting a cysteine showed a higher rate of sinuses of Valsalva dilation than missense mutations not affecting cysteine. However, no differences in cardiovascular involvement were observed when comparing the other mutation types [ 81 ].…”
Section: Genotype–phenotype Correlationsmentioning
confidence: 99%
“…There is a specific guideline for the interpretation of sequenced variants in the FBN1 Gene for Marfan Syndrome besides the American College of Medical Genetics (ACMG) guideline to help us identify novel mutations in FBN1 likely to cause MFS (Muiño-Mosquera et al, 2018). With the identification of FBN1 as the genetic basis of MFS (Stark et al, 2020), the hope for MFS patients' early diagnosis, preventive treatment, and elective surgery is feasible.…”
Section: Introductionmentioning
confidence: 99%